A case report of intracranial hypertension and aseptic meningitis: anti-tumor necrosis factor associated or juvenile idiopathic arthritis related - Akça, Ümmüşen Kaya; Sökmen, Okan; Bölek, Ertuğrul Çağrı; Demir, Selcan; Kılıç, Levent; Çevik, Işın Ünal; Bilginer, Yelda (The Turkish Journal of Pediatrics, 2021)
Background. The adverse effects of tumor necrosis factor alpha inhibitors (TNFi) are well characterized but rare adverse events are increasing day by day. Case. We presented an 18-year-old girl with rheumatoid factor positive polyarticular juvenile idiopathic arthritis (JIA) who developed fever, headache, and nausea after the second dose of adalimumab. In addition to her suspicious complaints for meningitis, she had bilateral papilledema and partial abducens nerve palsy. Leptomeningeal contrast enhancement was noted in magnetic resonance imaging (MRI) of the brain. Brain MRI venography was normal. The cerebrospinal fluid (CSF) opening pressure was high but CSF analysis was normal. She was diagnosed with non-infectious subacute meningitis. Since brain biopsy was not performed, no definite distinction could be made between TNFi related aseptic meningitis or cerebral involvement of JIA. Due to the onset of neurological complaints after initiation of adalimumab treatment and rare cerebral involvement in JIA, the drug-associated aseptic meningitis was likely to be responsible in our patient. Adalimumab was discontinued and methylprednisolone followed by methotrexate treatment were initiated. Her symptoms resolved and control brain MRI was normal. Conclusion. Pediatric rheumatologists should be aware of this potentially severe side effect of anti-TNF treatment.
Keywords: aseptic meningitis; intracranial hypertension; tumor necrosis factor alpha inhibitors